2013
DOI: 10.1007/s10096-013-1954-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic diversity of Pseudomonas aeruginosa in cystic fibrosis siblings in Qatar using AFLP fingerprinting

Abstract: Pseudomonas aeruginosa is one of the primary pathogens in patients with cystic fibrosis (CF) and a major cause of morbidity and mortality. Reports of the spread of epidemic or transmissible strains of P. aeruginosa within and across CF centers raised the possibility of clonal spread among siblings with CF. This work reports the genotypic relatedness of P. aeruginosa in CF patients with the CFTR I1234V mutation, and to determine whether the genotypes are identical among CF siblings and among different families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“… 18 26 By employing amplified fragment-length polymorphism molecular fingerprinting, a previous study has shown similar distribution of P. aeruginosa isolates among siblings and closely related families, indicating person-to-person transmission of P. aeruginosa within the same family or infection of P. aeruginosa possibly acquired from common environmental exposure. 26 The PFGE of P. aeruginosa isolates was largely in agreement with the diversity found by amplified fragment-length polymorphism fingerprinting in several previous studies that showed that siblings with CF frequently carry identical P. aeruginosa isolates. 18 , 27 29 …”
Section: Discussionmentioning
confidence: 96%
“… 18 26 By employing amplified fragment-length polymorphism molecular fingerprinting, a previous study has shown similar distribution of P. aeruginosa isolates among siblings and closely related families, indicating person-to-person transmission of P. aeruginosa within the same family or infection of P. aeruginosa possibly acquired from common environmental exposure. 26 The PFGE of P. aeruginosa isolates was largely in agreement with the diversity found by amplified fragment-length polymorphism fingerprinting in several previous studies that showed that siblings with CF frequently carry identical P. aeruginosa isolates. 18 , 27 29 …”
Section: Discussionmentioning
confidence: 96%
“…Abdul Wahab later on studied the prevalence of Candida dubliniensis [37] and examined the genetic relatedness of Pseudomonas aeruginosa among CF patients and siblings with CF [38] as well as among CF versus non-CF patients [39]. During the following year, researchers compared the accuracy of bacterial identification methods using matrix-assisted laser desorption/ionization–time of flight mass spectrometry [40].…”
Section: The History Of Cystic Fibrosis In Qatarmentioning
confidence: 99%